Livestock feed production and marketing in Central and North Rift Valley Regions of Kenya - Nangole, E.; Lukuyu, Ben A.; Franzel, Steven; Kinuthia, E.; Baltenweck, Isabelle; Kirui, Josephine (East Africa Dairy Development Project, 2013)
Availability and access to feed resources are important constraints to livestock productivity in East Africa. This study examined the production and marketing of livestock feeds in Central and North Rift regions in Kenya. Looking at existing fodder value chains to assess constraints and opportunities using the value chain approach, a rapid reconnaissance survey was conducted in which 93 actors were interviewed along the value chain in November 2010. Fodder marketing takes place at two levels: location (a cluster of 2-3 villages) and district. Trading at location level involved input sellers, producers selling directly to rural retailers, rural consumers, or if they were near major district towns, to wholesalers. District level trading involved traders who sourced for fodder outside the district and retailed to wholesalers in major consumer markets within districts and to a lesser extend retailed in local areas. Service providers such as transporters and feed processors operated at all levels. Input providers comprised of agrovet and general retail shops. Traders comprised of individual traders and cooperative societies. Feed trading is seasonal commonly occurring during the dry season with seasonal price variations at all levels. Feed price have increased by about 15% within the past year. In all the sites, local feed markets are dominated by livestock keepers selling excess fodder. There are few “specialized” fodder sellers, i.e. non livestock keepers who grew fodder as a source of income. Commonly traded feeds in the dry season were Rhodes grass, maize stovers, oat straws and Lucerne hay that were preferred due to longer storage period. Others forages were Napier grass and roadside harvested grass. Most traded fodder had low gross margins (GM) although foodfeed crops such as oats, sweet potato, etc tended to have higher GM. Actors reported an increasing demand for purchased fodder although they all operated in uncoordinated manner. Cooperative societies played a key role in linking buyers and sellers, stimulating demand and providing credit. Lack of input capital is perceived as a major constraint more than lack of market because demand for feed is strong during the dry season. This study concludes that there is need to promote feed marketing as a package alongside feed conservation, feed processing as well creating platform for that provide linkages for all actors to operate in coordinated way. Processing of feed is important to reducing bulkiness and handling costs hence easy storage and transportation. Provision of market information to producers and buyers is important to enhance and improve feed marketing systems.